Analysis of power and energy losses in power systems of electric bus battery charging stations - Jajczyk Jarosław (E3S Web of Conferences, 2017)
Two variants of electricity transmission from the Transfer-Switching Station (TSS) to the battery charging station were analysed in the paper. The first variant under analysis referred to the transmission of electricity via a three phase a.c. line with rated voltage of 15 kV. In the second variant of electricity transmission, the d.c. line with the working voltage of 1500 V was used. For both variants, lines and other equipment such as transformers, rectifier system and voltage stabilisation system in the battery charging station were modelled. For both solutions, analysis of energy per annum was conducted depending on the distance of the charging station from the TSS. On top of this, the simultaneous operation of several chargers was taken into account, which would correspond to the case of charging many buses at the same time from a single power line. The paper demonstrates that in the case of the analysed electricity transmission systems in the electric bus battery charging systems it is possible to use a more advantageous solution, which is characterised by reduced power and energy losses.